2015
DOI: 10.1002/pssb.201552490
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle self‐consistent GW study of AIN

Abstract: Recently, experimental fundamental quantities of a fine powder of rocksalt AlN (RS) at ambient pressure have been measured. The optical part of this experiment analyzes the phonon features observed by Raman scattering and infrared transmission. This new experimental RS measurement may provide access in the future to new experimental data on its band structure and this might make it worthwhile to reinvestigate the band structure with the best available newest methods. In this context, electronic and optical mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This method has been shown to provide significant improvements in the calculation of band gaps and band positions in a broad range of semiconductors. 59 61 …”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been shown to provide significant improvements in the calculation of band gaps and band positions in a broad range of semiconductors. 59 61 …”
Section: Computational Methodologymentioning
confidence: 99%
“…Here, we instead adopted the empirical hybrid QSGW (hQSGW) approach, in which 80% of the QSGW self-energy is combined with 20% of the LDA potential. This method has been shown to provide significant improvements in the calculation of band gaps and band positions in a broad range of semiconductors. …”
Section: Computational Methodologymentioning
confidence: 99%
“…12) In this paper, we present practical applications of PMT-QSGW with the ecalj package to a variety of materials. The present calculation results have not been presented yet, although PMT-QSGW with the ecalj package was already used in the preceding studies [13][14][15][16][17][18] and the minimum examination of PMT-QSGW was reported in Ref. 5.…”
Section: Introductionmentioning
confidence: 99%